Topological Methods for Enhancing Ecosystem Management and Biodiversity Conservation - Dr.A.Manshath,; Dr. Sachin Sukhadeo Bere,; Dr. Brinda Halambi,; Durai Ganesh A,; Dr. Shreni Diwakar,; Dr.D.Rajinigirinath, (The Bioscan, 2024)
Ecosystem management and biodiversity conservation face increasing challenges in a world of rapid environmental change. Topology, a branch of mathematics studying shapes and their properties, offers a novel approach to understanding and managing complex ecosystems. This paper explores the application of topological methods in analyzing ecological data, revealing hidden patterns, connectivity, and resilience within ecosystems. We discuss key topological concepts like persistent homology and Mapper, highlighting their applications in identifying critical habitats, assessing landscape connectivity, and predicting ecosystem responses to disturbances. We also examine the challenges and limitations of these methods, emphasizing the importance of integrating topological insights with ecological knowledge and conservation practices. This paper underscores the potential of topological methods to enhance our understanding of ecosystems and contribute to more effective conservation strategies.